Self-reported health-related quality of life in kindergarten children: psychometric properties of the Kiddy-KINDL. Issue 7 (July 2015) - Villalonga-Olives, E.; Kiese-Himmel, C.; Witte, C.; Almansa, J.; Dusilova, I.; Hacker, K.; von Steinbuechel, N.
Abstract Objectives To assess the psychometric properties of the German self-reported version of the Kiddy-KINDL that measures Health Related Quality of Life (HRQoL) in 3 to 5 year old kindergarten children. Study design The population of the study comprised baseline data of a longitudinal study whose main aim is to investigate self-reported health outcomes in young children (N = 317). Methods Missing values, the distribution of data, internal consistency (Cronbach's alpha and Guttman's lambda), and reliability (split half and two weeks test-retest) were analysed. To assess discriminant validity, mean differences were tested splitting the sample regarding socio-emotional competences (VBV 3-6), age and gender. Structural validity was investigated with Confirmatory Factor Analysis (CFA). Results Mean HRQoL was 69.79 (SD 16.84). Overall missing values were 8.1%, overall Cronbach's alpha was 0.75 and overall Guttman's lambda was 0.77; for the whole scale Spearman-Brown test for split half reliability resulted in 0.80 and ICC for test-retest in 0.83. Discriminant validity investigation differentiated groups with high and low socio-emotional competence and those children who were 4.5 years or older, compared to the younger ones. Differences between boys and girls were also found. CFA suggested two main dimensions: physical and socio-emotional. Conclusion This preliminary validation of the Kiddy-KINDL in very young children shows satisfactory psychometric properties. However, results of the Cronbach's alpha, Guttman's lambda and the CFA depicted problems, mainly in the psychological dimension. Due to these we recommend to use the Kiddy-KINDL as an instrument with only two dimensions. Further studies in general population samples are needed.